(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2018)
This paper reports on the application of age cohorts to the theory of social networks in a study of language choices of Tamil city dwellers in Kuching, Sarawak located on the island of Borneo. This study, which adopts Milroy’s (1980) social networks, focuses mainly on code choices made in the spoken discourse of multilingual Tamils of different age cohorts. Our analysis of data gathered from a one-shot survey and supported by face-to-face interviews shows variations in code choices by age cohort. Code selections within and across the different age cohorts in the home and friendship domains denote the influence of age and social networks among minority Tamils.